A case of Acute Transverse Myelopathy following Measles-Mumps-Rubella (MMR) vaccination in Malaysia. - Mohd Fakharuddin, Mohd. Feizel Alsiddiq
Objective : To describe the clinical course case of Acute Transverse Myelopathy following an MMR vaccination and the review the literature regarding association of transverse myelitis and vaccination.